2021
DOI: 10.1111/jnu.12750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurse‐led nonpharmacological pain interventions for patients with cancer: A systematic review and meta‐analysis

Abstract: Purpose The purposes of this study were to review the types of nurse‐led nonpharmacological pain interventions (NPI) offered to cancer patients and/or family caregivers, and to determine a comprehensive and robust estimate of the effect size of nurse‐led NPI for cancer patients on various pain‐related outcomes. Design Systematic review and meta‐analysis. Studies assessing nurse‐led NPIs targeting cancer patients and published between January 2008 and December 2020 were identified by searching multiple literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…A meta-analysis of nurse-led non-pharmacological pain interventions found that although these interventions had low long- to moderate short-term effects, they significantly reduced patients’ pain, improved their knowledge of pain management, reduced barriers to pain management and pain coping, and improved other physical and emotional symptoms. 53…”
Section: Non-pharmacological Pain Managementmentioning
confidence: 99%
“…A meta-analysis of nurse-led non-pharmacological pain interventions found that although these interventions had low long- to moderate short-term effects, they significantly reduced patients’ pain, improved their knowledge of pain management, reduced barriers to pain management and pain coping, and improved other physical and emotional symptoms. 53…”
Section: Non-pharmacological Pain Managementmentioning
confidence: 99%